Calcination Method of 45Ca Samples for Isotope Ratio Analysis via Liquid Scintillation. Issue 4 (21st February 2019) - Videla, Ximena; Rojas-Silva, Ximena; Nario, Adriana; Arias, María Ignacia; Bonomelli, Claudia
ABSTRACT: This study was designed to optimize calcium-45 ( 45 Ca) sample preparation method in a Liquid Scintillation Counter (LSC) for use with vegetables and soil samples. Different tests were conducted on fruit and soil samples to determine the best conditions related to drying, time and centrifuge speed (rpm) after calcination at 450°C and 550°C for vegetable and soil samples, respectively. The homogeneity of samples, linearity, detection and quantification limits were also determined. The quench curve was calculated to establish the parameters to program the LSC. Six 45 Ca sample replicates were measured with a coefficient of variation (CV) of 1.74%, which indicates good sample homogeneity. The method is linearity over the range of activity studied for 0–30, 000 disintegrations per minute (dpm). Our results suggest that the optimum homogenized sample preparation for calcination purposes was lyophilization. Techniques using 45 Ca applied to soil and plant tissues are promising tracers of Ca in plants, which can be very useful for the study of Ca kinetics in plants and can serve to guide efficient fertilization programs.